Synthesis of Eight‐Membered Nitrogen Heterocycles via a Heterogeneous PtI2‐Catalyzed Cascade Cycloaddition Reaction of δ‐Aminoalkynes with Electron‐Deficient Alkynes. Issue 7 (9th March 2020) - Li, Xinhong; Wang, Songmeng; Wang, Hongkai; Wang, Weilin; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract: A novel heterogeneous PtI2 ‐catalyzed cascade reaction of δ‐aminoalkynes was developed for the synthesis of various eight‐membered nitrogen heterocycles in excellent yields. The reaction proceeds via a hydration of δ‐aminoalkynes and subsequent intramolecular cyclization and intermolecular addition as well as ring‐expansion cascade reaction with another electron‐deficient alkynes. This method has the advantages of simple operation and mild reaction conditions. And the simple PtI2 with no any supports could be readily recycled through simple centrifugation without substantial loss of activity in 1, 2‐dichloroethane (DCE). The recyclability of PtI2 may be ascribed to its insolubility in DCE. The reaction constitutes a formal [6+2]‐cycloaddition. Abstract :